PEROLEHAN SATUAN RUMAH SUSUN DI ATAS TANAH HAK GUNA BANGUNAN OLEH PASANGAN SUAMI ISTRI YANG BERBEDA KEWARGANEGARAAN: Acquisition Of A Flat Unit On Land Use Right By Married Couple Of Different Nationality - Aris Dwi Saputro; Anda Setiawati (Faculty of Law, Universitas Trisakti, 2025)
A prenuptial agreement must be executed by a married couple of different nationalities in order to acquire and control ownership of a condominium unit constructed on land with HGB. A legal issue arises due to the fact that not all such couples have entered into a prenuptial agreement. The legal issues formulated in this research are: (1) How is the ownership of condominium units by foreign citizen regulated? and (2) how can a married couple of different nationalities who have not executed a prenuptial agreement acquire a condominium unit? The research method used is a normative legal research, which is based on secondary data or library-based research. Based on the discussion, the conclusion is that the ownership of condominium units built on land with HGB by married couples of different nationalities is permitted, provided that the proprietary right over the condominium is not in the form of HMSRS, but rather in the form of HPSRS. A foreign individual who intends to acquire and control a condominium unit in Indonesia may only do so under a Right of Use or leasehold arrangement.